122k views
1 vote
What is the difference?

What is the difference?-example-1

1 Answer

5 votes

Answer:

Option b) is correct.

The difference of given expression is


\left((2x+5)/(x^2-3x)\right)-\left((3x+5)/(x^3-9x)\right)-\left((1x+1)/(x^2-9)\right)=((x+2)(x+5))/((x^3-9x))

Explanation:

Given expression is


\left((2x+5)/(x^2-3x)\right)-\left((3x+5)/(x^3-9x)\right)-\left((1x+1)/(x^2-9)\right)

To find their difference


\left((2x+5)/(x^2-3x)\right)-\left((3x+5)/(x^3-9x)\right)-\left((x+1)/(x^2-9)\right)

The expression can be written as below


\left((2x+5)/(x^2-3x)\right)-\left((3x+5)/(x^3-9x)\right)-\left((x+1)/(x^2-9)\right)=\left((2x+5)/(x (x-3))\right)-\left((3x+5)/(x(x^2-9))\right)-\left((x+1)/(x^2-9)\right)


=\left((2x+5)/(x(x-3))\right)-\left((3x+5)/(x(x^2-3^2))\right)-\left((x+1)/(x^2-3^2)\right)


=\left((2x+5)/(x(x-3))\right)-\left((3x+5)/(x(x+3)(x-3))\right)-\left((x+1)/((x+3)(x-3))\right) (using
a^2-b^2=(a+b)(a-b))


=((2x+5)(x+3)-(3x+5)-(x+1)x)/(x(x+3)(x-3))


=(2x^2+6x+5x+15-3x-5-x^2-x)/(x(x+3)(x-3))


=(x^2+7x+10)/(x(x+3)(x-3))


=((x+2)(x+5))/(x(x+3)(x-3))


=((x+2)(x+5))/(x(x^2-3^2)) (using
a^2-b^2=(a+b)(a-b))


=((x+2)(x+5))/(x(x^2-9))


=((x+2)(x+5))/((x^3-9x))

Therefore
\left((2x+5)/(x^2-3x)\right)-\left((3x+5)/(x^3-9x)\right)-\left((1x+1)/(x^2-9)\right)=((x+2)(x+5))/((x^3-9x))

Option b) is correct.

The difference of given expression is


\left((2x+5)/(x^2-3x)\right)-\left((3x+5)/(x^3-9x)\right)-\left((1x+1)/(x^2-9)\right)=((x+2)(x+5))/((x^3-9x))

User Merri
by
6.0k points